2021
DOI: 10.1371/journal.pone.0253788
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic response during a live action-observation and action-execution task: A fNIRS study

Abstract: Although many studies have examined the location of the action observation network (AON) in human adults, the shared neural correlates of action-observation and action-execution are still unclear partially due to lack of ecologically valid neuroimaging measures. In this study, we aim to demonstrate the feasibility of using functional near infrared spectroscopy (fNIRS) to measure the neural correlates of action-observation and action execution regions during a live task. Thirty adults reached for objects or obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…FNIRS findings suggested that bilateral superior parietal lobule (SPL), bilateral inferior parietal lobule (IPL), right supra-marginal region (SMG) and right angular gyrus (AG) are candidate regions of the human AON, as previously reported in Miguel et al 53 . Figure 3 represents a summary of our findings.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…FNIRS findings suggested that bilateral superior parietal lobule (SPL), bilateral inferior parietal lobule (IPL), right supra-marginal region (SMG) and right angular gyrus (AG) are candidate regions of the human AON, as previously reported in Miguel et al 53 . Figure 3 represents a summary of our findings.…”
Section: Resultssupporting
confidence: 71%
“…Each trial was followed by a 20 s recovery period during which the participant passively viewed a moving pendulum. For further information on the paradigm we used please see Miguel et al 53 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations